Age-related and individual features of the HPA axis stress responsiveness under constant light in nonhuman primates - Goncharova, Nadezhda; Chigarova, Olga; Oganyan, Tamara (Frontiers in Endocrinology, 2023)
The hypothalamic-pituitary-adrenal (HPA) axis is a key adaptive neuroendocrine system, dysfunction of which plays an important role in the increasing incidence of stress-dependent age-related pathology. Among the environmental factors effecting increase age-related diseases, great importance is given to disturbances of the light-dark schedule, particularly with increased illumination at night. While disruption of the light-dark schedule has long been recognized as a powerful behavioral stressor, little is known regarding stress reactivity of the HPA under constant light (CL) conditions, especially with aging and depending on the features of stress behavior. The purpose of this investigation was to study the age-related and individual features of the HPA axis response to acute stress exposure (ASE) under chronic CL in nonhuman primates that are known to differ in behavioral responsiveness to stress. Young and old female rhesus monkeys (with control standard behavior or anxiety and depression-like behavior) were exposed to CL (24 h light/day, 330-400 lux for 4 to 8 weeks). Control young and old monkeys were exposed to standard lighting (SL) with natural light during the day and darkness at night. All animals were subjected to ASE (restriction of mobility for 2 hours), functional tests with corticotrophin-releasing hormone and arginine-vasopressin, and study of circadian rhythms of cortisol and pineal melatonin secretion. For the first time an inhibitory effect of CL on the reaction of the adrenal cortex to ASE was revealed in all individuals, regardless of age and preexisting behavior stress reactivity, the mechanisms of which were age-dependent: due to inhibition of the pituitary ACTH secretion in young animals and mainly not affecting the ACTH secretion in old individuals. There were no significant changes in melatonin secretion both in young and old animals. The observed CL inhibition of adrenal cortical reactivity to ASE may be useful to correct increased vulnerability to ASE observed in individuals with preexisting anxiety and depression-like stress behaviors. On the other hand, the CL induced decrease in adrenal stress reactivity of behaviorally normal animals suggests a potential risk of reducing the adaptive capacity of the organism under conditions of continuous light exposure.